'Letters to the editor': the relationship between multinationality and firm performance in emerging markets. Issue 4 (2nd October 2021) - Mullen, Cormac
Abstract: Addressing previously recognised shortcomings in the multinationality-performance literature, we find no evidence of a consistent relationship between a company's level of internationalisation and its financial or stock-market performance for 1299 emerging-market firms from 31 countries over an 8-year period from 2011 to 2018. We contribute empirically by applying dynamic gauges of multinationality and a seldom-used combination of sector-relative financial and market-based performance measures to a dataset of developing-nation companies for the first time. We conclude that like its developed-market peers, an emerging-market company's level of multinationality does not affect its performance either positively or negatively, as is evident in the sheer variety of 'letter-shape' multinationality-performance results shown here and in the literature.